1991
DOI: 10.1017/s002211209100349x
|View full text |Cite
|
Sign up to set email alerts
|

A parametric acoustic instability in premixed flames

Abstract: We present an experimental and theoretical investigation of some aspects of the coupling between a premixed laminar quasi-planar flame front and acoustic standing waves in tubes. A multidimensional instability of the front arises from its interaction with the oscillating field of acceleration. This instability can be described by the Clavin–Williams laminar wrinkled flame theory in which the periodic acceleration created by the acoustic field is added to the acceleration due to gravity. As first suggested by M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
125
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(144 citation statements)
references
References 13 publications
18
125
1
Order By: Relevance
“…(18) may be satisfied only in a restricted frequency range, within which the phase criterion arg (F(ω)) = π (Eq. (16)) must also be satisfied to trigger an unstable ITA mode 7 .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…(18) may be satisfied only in a restricted frequency range, within which the phase criterion arg (F(ω)) = π (Eq. (16)) must also be satisfied to trigger an unstable ITA mode 7 .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In particular, it prevents the development of singularities of the front shape such as the edge points which would occur otherwise [15], leading to discontinuities in the values of the flow variables or their derivatives. That λ c often exceeds the actual thickness of the flame preheat zone significantly [16] has yet another virtue: the Reynolds number based on λ c and the fuel properties is typically over ∼ 10 2 , and hence is fairly large when based upon the width (> λ c or ≫ λ c ) of the channel where the flame studied below is meant to propagate. It then makes sense to model the flame as a surface (or line in 2-D) equipped with a local λ c -dependent propagation law, and embedded in ideal fluid flows.…”
Section: Integral Representation Of the Flow Equationsmentioning
confidence: 99%
“…He reported four distinct regimes of downward-propagating flames in a tube: (1) a curved flame with no acoustic sound just after ignition; (2) a primary acoustic instability with a flat flame surface when the flame has reached the lower half of the tube; (3) a violent secondary acoustic instability with a corrugated flame; and (4) turbulent flame. The secondary acoustic instability has been distinctly studied experimentally [2,3]. The physical initiation mechanism of this instability is periodic acceleration of the flame separating dense and tenuous regions, which is similar to Faraday instability [4].…”
Section: Introductionmentioning
confidence: 99%
“…An analytical analysis of this mechanism was further performed by Pelcé and Rochwerger [11] in connection with the experiments conducted by Searby [1]. They studied the coupling with variation in the flame surface area produced by the presence of an initial curved structure due to D-L instability and demonstrated that the growth rate of the primary acoustic instability is proportional to (ak) 2 , where a is an amplitude and k is a wave number of the curved flame. For this study, they used a more complete model for flame dynamics that adopted stability limits of the D-L instability [9] and gravity effects into the problem in order to estimate a situation close to that of real propagating flames.…”
Section: Introductionmentioning
confidence: 99%